Modification of PVC film and study the effect of glass transition temperature and biocompatibility - Misra N.; Panda H.S.; Kapusetti G.; Jaaiswal S.; Chooramani Gopal S.; Sharma U.S. (My University, 2025)
Medical grade polyvinyl chloride) surface was modified with sodium sulfide by nucleophilic substitution of sulfur atoms in presence of a phase-transfer catalyst. Surface modified PVC was characterized with fourier transform infrared spectroscopy, scanning electron microscope, and differential scanning calorimetry. Migration or leaching of the plasticizer, di-(2-ethylhexyl) phthalate, was examined in petroleum ether followed by differential scanning calorimetry. The leaching test was also earned out with poly(ethylene glycol)-400 (PEG-400). The surface of modified PVC film was found to be extremely migration resistant of DEHP in petroleum ether and PEG-400. Clotting time measurement was performed on both modified and unmodified PVC, and observed almost equal value. It was reflected that there is no major change on its thrombogenicity. Further, blood compatibility of modified PVC was examined through haemolysis assay and suggested that it is nontoxic material for biomedical applications. © MD Publications Pvt. Ltd.